2016
DOI: 10.18632/oncotarget.12501
|View full text |Cite
|
Sign up to set email alerts
|

Impact of HPV infection on oral squamous cell carcinoma

Abstract: BackgroundHead and neck squamous cell carcinomas (HNSCC) are often divided by their aetiology. Noxae associated collectives are compared with the human papilloma virus (HPV)-associated group, whereas different localisations of oral (OSCC) and oropharyngeal (OPSCC) squamous cell carcinomas are mostly discussed as one single group. Our aim was to show that classification by aetiology is not appropriate for OSCC.ResultsHPV DNA was detected by PCR in 7 (3.47%) patients, and we identified 12 (5.94%) positive (+) ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 47 publications
1
31
0
Order By: Relevance
“…Kauppila et al suggested that high TLR 5 expression is associated with high rate of mortality and recurrences in oral mobile tongue SCC [17], and Ni et al suggested that high expression of TLR 7 could improve survival in oral SCC [21]. Although they did not study the HPV status in their series, HPV negativity in oral SCC is highly probable [37]. Therefore, our result showing that TLR 5 and 7 expression patterns are not associated with survival in HPV-negative OPSCC is in contrast with these findings.…”
Section: Discussionmentioning
confidence: 99%
“…Kauppila et al suggested that high TLR 5 expression is associated with high rate of mortality and recurrences in oral mobile tongue SCC [17], and Ni et al suggested that high expression of TLR 7 could improve survival in oral SCC [21]. Although they did not study the HPV status in their series, HPV negativity in oral SCC is highly probable [37]. Therefore, our result showing that TLR 5 and 7 expression patterns are not associated with survival in HPV-negative OPSCC is in contrast with these findings.…”
Section: Discussionmentioning
confidence: 99%
“…As intraoperative controls, an intraoperative margin control and frozen sections were also obtained in each tumour operation. As previously described ( 30 ), adjuvant cisplatin-based chemoradiation was performed in cases of lymph node metastasis, extracapsular spread, tumour infiltration of the bone, tumours of extended size (T2-T4) and positive microscopic resection margins (R1) according to the S3 German guidelines for oral cancer. Patients were excluded from the study if no curative surgical treatment was performed and the primary treatment was radiochemotherapy.…”
Section: Methodsmentioning
confidence: 99%
“…The centre and invasive front of tumours of all study participants were included in the TMA ( 30 , 31 ). The tissues were formalin-fixed and paraffin-embedded in blocks ( 30 , 31 ). Two pathologists analysed the areas to be represented in the TMA.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Unfavorably, the incidence is increasing with approximately 300,000 new reported cases annually, or 2.1% of the world total [1]. Risk factors include smoking, especially in combination with heavy alcohol consumption, nonvegetarian diet, poor oral hygiene, poor dentition [2], and in rare cases infections with human papilloma virus (HPV) [3].…”
Section: Introductionmentioning
confidence: 99%